2023
DOI: 10.3390/medicina59091583
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Post-COVID Syndrome and the Burden of Comorbidities Assessed Using the Charlson Comorbidity Index

Lorenzo Falsetti,
Vincenzo Zaccone,
Luca Santoro
et al.

Abstract: Introduction: The post-COVID-19 syndrome is a clinical entity characterized by the manifestation of signs and symptoms that develop after the acute phase of COVID-19, which persist for a duration of more than 12 weeks and are not explained by any alternative diagnosis. It has been observed that individuals with pre-existing chronic diseases, including cardiovascular and pulmonary diseases, are at a greater risk of developing post-COVID-19 syndrome. The Charlson Comorbidity Index (CCI) is a useful tool employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We found no statistically significant relationship between the incidence of post-COVID-19 syndrome and the presence of any comorbidity. A 2023 study by Falsetti et al [ 18 ] analyzed 3 years of data to assess whether the burden of comorbidities correlates with COVID-19 outcomes. Their nationwide analysis suggested that the development of post-COVID-19 symptoms was associated with a higher burden of comorbidities ( p <0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…We found no statistically significant relationship between the incidence of post-COVID-19 syndrome and the presence of any comorbidity. A 2023 study by Falsetti et al [ 18 ] analyzed 3 years of data to assess whether the burden of comorbidities correlates with COVID-19 outcomes. Their nationwide analysis suggested that the development of post-COVID-19 symptoms was associated with a higher burden of comorbidities ( p <0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…There is a connection between comorbidities and LC. Falsetti and colleagues established a strong correlation between comorbidities and the subsequent development of LC [82]. Their findings stress that patients with hypertension, obesity, diabetes, chronic lung disease, and heart disease are dramatically impacted by COVID-19 and are more likely to develop LC [82].…”
Section: Nutrition Diabetes and Health Outcomesmentioning
confidence: 99%
“…Falsetti and colleagues established a strong correlation between comorbidities and the subsequent development of LC [82]. Their findings stress that patients with hypertension, obesity, diabetes, chronic lung disease, and heart disease are dramatically impacted by COVID-19 and are more likely to develop LC [82]. Possible explanations for such associations included an exacerbated immune response and immune dysfunction, endothelial dysfunction, and acute illness.…”
Section: Nutrition Diabetes and Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation